2005
DOI: 10.5688/aj690115
|View full text |Cite
|
Sign up to set email alerts
|

Students' Motivations for Class Attendance

Abstract: Many faculty members, from a variety of disciplines and universities, complain about students' class attendance. Lack of class attendance can have a multitude of consequences, for both the faculty members and students. Faculty members may find themselves repeating information, directions, or explanations numerous times and in a variety of delivery formats. As a result, faculty members may require students who miss information presented in class to get that information from classmates. College students, after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 6 publications
2
60
0
Order By: Relevance
“…Student must be physically present and mentally receptive for learning to occur. 46 Students who choose to skip lecture-based teachings and rely solely on other modes of learning with the class subject are less likely to retain relevant knowledge related to the subject as compared to those who attend the class; subsequently those who absent perform poorly on the examinations. 11 One study showed that 80% of medical students chose to attend specific lectures dependent on the lecture topic itself, while another found that 69% of students cite interest in the topic as a key reason for attendance.…”
Section: Factors Related To Teaching Stuffmentioning
confidence: 99%
See 1 more Smart Citation
“…Student must be physically present and mentally receptive for learning to occur. 46 Students who choose to skip lecture-based teachings and rely solely on other modes of learning with the class subject are less likely to retain relevant knowledge related to the subject as compared to those who attend the class; subsequently those who absent perform poorly on the examinations. 11 One study showed that 80% of medical students chose to attend specific lectures dependent on the lecture topic itself, while another found that 69% of students cite interest in the topic as a key reason for attendance.…”
Section: Factors Related To Teaching Stuffmentioning
confidence: 99%
“…46 The lecture-based teachings are capable to enhance skills related to cognitive, affective and psychomotor. 47 Historically, reports suggested that attendance is better at lectures compared to small group teaching.…”
Section: Factors Related To Teaching Material/strategymentioning
confidence: 99%
“…It is important in higher education as this does not only affect the absent student and his/her academic success, but it can also affect the lecturers, other present students and thus the whole learning environment at school (Salisa and others, 2009). School is a social organization and interaction among students and their instructors is very important because the school lets them socialize professionally by observing the others, especially faculty members and recognizing them as role models (Fjortoft, 2005;Hammer and others, 2003). It is stressed that those who miss the class frequently are the ones who do not realize that the classroom or school is a community that they belong to and must be a part of and that when they do not attend classes, their learning level decreases and it becomes difficult to reach desired academic goals (Cronon, 1998;Brown, 2002).…”
Section: Absenteeism and Academic Successmentioning
confidence: 99%
“…Part of the responsibility of being a faculty member is to identify what motivates students and to adapt teaching styles so that they are conducive to effective learning. In a study of pharmacy students by Fjortoft,9 motivators to attend live class lectures included the lack of a conclusive handout, the expectation that new information would be presented in class that was not included in the handout, and faculty application of information to solve real problems. In the same study, negative variables that contributed to poor classroom attendance included the class being either before or after an examination in another course, faculty members who do not supplement their provided notes, personal logistics, and extended breaks of 2 hours or more between classes.…”
Section: Introductionmentioning
confidence: 99%